Tracking of The Most Significant Laboratory Parameters For The Identification of Covid-19: An Overview on The Different Blood Tests - Ali, Seenaa (Kurdistan Journal of Applied Research, 2020)
An outbreak of 2019 novel coronavirus disease (COVID-19) began in China during December 2019 which unexpectedly spread to other countries and caused high mortality all over the world. COVID-19 disease primarily manifests as a respiratory tract infection. However, emerging data indicate that it should be regarded as a systemic disease for affecting multiple systems such as cardiovascular, respiratory, gastrointestinal and immune system. There is an accelerated need for detecting the laboratory tests that can aid in identifying infected people and asymptomatic carriers to control the virus transmission process. Although the clinical manifestation of COVID-19 has been widely defined, an overview of the most significant laboratory findings in patients with COVID-19 infection is still limited. Elevation was the predominate result among most of the laboratory parameters while a few decreased in value. Laboratory data have shown that most patients had a decrease in lymphocyte count, Eosinophils count and albumin level. Also, laboratory data recorded an elevation in Leukocyte, ESR, PT, D-dimer, PCT, CRP, ALT, AST, Bilirubin, Creatinine, CK, LDH, Ferritin, Troponin, Myoglobin, IL-6, IL10 and TNF. In general, the parameters had more prominent laboratory abnormalities in severe cases than with non-severe cases. It is well known that laboratory tests results play an important role and can support the early diagnosis of many diseases. This study was carried out to review the abnormalities among the laboratory tests and track the parameters that showed a frequently significant result supporting the primary detection of SARS-COV-2 infection.